Synthesis of Novel 2-Amino Thiazole Derivatives and Salicyaldehyde based Ligand to have Biological Activity (Journal of Advances and Scholarly Researches in Allied Education, 2024)
In inorganic chemistry, Schiff bases and complexes come in a variety of forms. Therefore, the discovery of new organic and inorganic compounds with remarkable anti-fungal, anti-bacterial, and anticancer characteristics represents a major advancement in biochemistry, pharmacy, and medicine. All of the chemicals that were employed in this study were A.R. grade. The following materials provided by SD's fine chemical Ltd. and Merck chemicals, Mumbai were utilised impurification: methanol, calcium hydroxide, sodium acetate, thiourea, ethylacetoacetate, benzoyl chloride, acetyl chloride, 1,4-dioxane, and sulfuric acid. Additionally, this Schiff base may combine with the ions of several transition metals, such as Ni(II), Cu(II), Co(II), and Cd(II), to create complexes. In addition to chemical analysis, conductivity, and magnetic tests, we further characterized the complexes using electronic and infrared spectroscopy in order to examine their structures. Every compound's antibacterial activity was evaluated. In the agar cup test method, all of the Schiff base metal complexes had a moderate level of antibacterial activity. Spectroscopic data suggests that these complexes are all of type ML2.(H2O)2 (M=Mn, Fe, Co, Ni, and Cu).